Pharmacodynamics of mutant-IDH1 inhibitors in glioma patients probed by in vivo 3D MRS imaging of 2-hydroxyglutarate - Ovidiu C. Andronesi (Nature Portfolio, 2018)
Inhibitors of mutant isocitrate dehydrogenase 1 (IDH1) entered recently clinical trials for treatment of gliomas. Here, the authors apply a MRS imaging method for 2HG detection and assessement of the pharmacodynamic effects of the mutant IDH1 inhibitor (IDH305) in 8 mutant IDH1 glioma patients.